Glappet i den svenska vargattityden - en fråga om närhet till naturen? - Nordquist, Sofia (SLU/Dept. of Animal Environment and Health, 2014)
Humans attitudes towards different animals are very complex were culture, genetic, psychology and evolution are some of the factors that influence. The order of animals that can provoke the most intense and extreme attitudes, both positive and negative, are the carnivores. Wolves are a constant debate in Sweden and even though a big part of the population are neutral towards the wolf, a clear friction of the attitudes can be seen. Some factors that have been seen to influence the attitude are age, education and the size of the hometown. The aim of this study is to investigate whether outdoor activities, time spend in rural areas, and time spent in a weekend cottage, also correlate with attitude towards wolf. A survey were sent to 15 317 individuals in six counties of Sweden, which gave an answering frequency of 46-56 % in county level. The result shows that four of the fifteen examined outdoor activities have a positive correlation with the attitude towards wolf. This means that people that bicycle, ride, go skiing or snowboarding, generally have a more positive attitude then those that do not. The activity with the strongest connection is however not to take a hike for 1-3 hours which includes a significant more positive attitude. Other activities with a negative correlation with attitude towards wolf are to take a hike for the whole day, hike with camping, hunting, fishing, cross-country skiing and riding a snowmobile. This means that people performing these activities generally have a more negative attitude then those that do not. A negative correlation can also be seen between time spend in rural areas and the attitude towards wolf, which indicate that people spending less time in rural areas have a more positive attitude. This correlation is however very weak and can therefore be questioned. No conclusion can be drawn between time spend in a weekend cottage and attitude towards wolf. That the result presented in this study argue against previous research on a positive correlation between proximity to nature ...